NEEDS ASSESSMENT FOR ESTABLISHING FACULTY DEVELOPMENT PROGRAM IN A PRIVATE MEDICAL COLLEGE AT LAHORE - Manzoor, Iram; Zeeshan, Shamia; Iqbal, Amina; Sarfraz, Fahad (Journal of Ayub Medical College Abbottabad, 2018)
Background: Needs assessment helps in situation analysis and setting priorities for establishing a faculty development program to ensure quality improvement in education. The objective of this study was to identify areas for faculty development in order to incorporate them in continuingmedical education program. Methods: It was a cross sectional survey conducted from 2014 to 2015 in Fatima Memorial Hospital College of Medicine and Dentistry, Lahore, Pakistan. A non-probability consecutive sampling technique was used to include 195 faculty members from Medical & Dental College of all cadres. Data was collected through a self-administered questionnaire & analysed using SPSS 20. Chi square was applied and p-value of ‰¤0.05 was considered to be significant. Results: Out of 194 participants, 133 belonged to clinical departments and 61 to basic Sciences, with a higher proportion of female faculty members. (p=0.025). Importance of DME was recognized by 97% clinical and 95.1% basic science faculty. Faculty development program was considered essential by 69.1% of the clinical faculty & 30.9% of the basic faculty. (p=0.185). The priority areas identified were educational psychology (p=0.030), teaching skills (p=0.341), assessment techniques (p=0.296), educational research (p=0.849), management skills (p=0.797), work-based ethics & conduction of meeting. (p=0.01 & p=0.003). About 71.25% of the clinical teachers and 28.8% of the basic subject teachers have never attended any medical education program (p=0.001). The area of highest motivation was teaching (p=0.002), research (p=0.052), patient care (p=0.001) and administration (p=0.870). Conclusion: This survey reinforces the need of an effective faculty development program targeting training in teaching methodologies and assessment tools. Keywords: Need assessment; Faculty development; Educational research; Pakistan